Hur väl svarar produktionen mot de krav marknaden ställer? – Framtagande av strategiska riktlinjer för produktionen på Procordia Food AB - Klingberg,Linda; Lövgren,Johanna (2007)
Problem description To develop strategic guidelines for the production that are in line with the vision and marketing strategies of the company. Purpose The purpose is two folded. The first part aims to facilitate future strategic decisions concerning manufacturing. The second is to illuminate why the company should take the manufacturing strategy into consideration when taking other strategic decisions. Method The study in this master thesis had a deductive approach since a theoretical framework was developed and then applied to reality. The frame of reference that has been used is developed by Terry Hill and shows how manufacturing decisions should be a part of the strategic direction of the company as a whole. To succeed with this he proposes a well established work method. The primary sources have been collected through interviews and quantitative data collection and the secondary sources through literature studies. Conclusion Procordia Food is in large a market driven company. Market demands are constantly changing and not the same for all products. This makes manufacturing increasingly complex. The factories are often constructed to meet large volume demands. Current markets are not growing and the product range is increasing which creates a mismatch between markets and manufacturing. So far the mismatch has been handled by building up stocks, which – in long-term – is not sustainable. In short-term some of the mismatches can be handled through changes in infrastructure. However for a long-term competitiveness the manufacturing, including infrastructure and processes, has to become more flexible
Keywords: Marketing strategies; orderwinners & qualifiers; manufacturing’s current performance; process choice; infrastructure; manufacturing strategies